Effectiveness of Prolotherapy for Chronic Musculoskeletal Conditions - Saurabh Agarwal; Abhishek Nagaich; Nikhil Jain; Arvind Kumar Shah (Journal of Orthopedics, Traumatology and Rehabilitation)
Prolotherapy is one of the injection-based alternative therapeutic options for the treatment of chronic musculoskeletal pain. However, for chronic musculoskeletal conditions, corticosteroid and local anesthetic preparation like Lignocaine is widespread and initial injection therapy of choice. There are several other techniques also such as autologous whole blood, platelet-rich plasma, bone marrow, dry needling, and extracorporeal wave therapy. In prolotherapy, a very small amount of irritant or sclerosing solution is injected into joint space, ligament, or tendon insertion sites as a complementary medical treatment over several treatment seasons. Hyperosmolar dextrose, phenol–glycerine–glucose, and morrhuate sodium are the three most commonly used prolotherapy solutions. There are several studies and evidence available regarding the efficacy of prolotherapy over various musculoskeletal conditions such as chronic low back pain, osteoarthritis of joints, subluxation and joint instability, ligament laxity, hypermobility of joints, and tendinopathy. The efficacy of prolotherapy for different musculoskeletal conditions with different injections is different, and the precise mechanism of prolotherapy effect is still not clear, so further studies and clinical trials are recommended.